2016
DOI: 10.1002/jms.3774
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of colloidal graphite as a matrix for matrix‐assisted laser desorption/ionisation mass spectrometry of low molecular weight analytes

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms MALDI, colloidal graphite, matrix suppression, small molecules, matrix. AbstractThe analysis of low molecular weight compounds by Matrix-Assisted Laser Desorption/Ionisation mass spectrometry is problematic due to the interference and suppression of analyte ionisation by the matrices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…This is in accordance with what has previously been observed when comparing graphite matrices to organic matrices. [10][11][12] In negative ion mode analysis, the organic matrices generally performed very poorly (as expected) often with no analyte-related species observed. Spectra were almost totally dominated by the deprotonated ions of the matrices themselves, with little signal resulting from the analytes.…”
Section: Resultssupporting
confidence: 58%
“…This is in accordance with what has previously been observed when comparing graphite matrices to organic matrices. [10][11][12] In negative ion mode analysis, the organic matrices generally performed very poorly (as expected) often with no analyte-related species observed. Spectra were almost totally dominated by the deprotonated ions of the matrices themselves, with little signal resulting from the analytes.…”
Section: Resultssupporting
confidence: 58%
“…Carbon based matrices can be effectively employed in MALDI MS experiments 25 ; therefore, it may be speculated that carbon black fingermark enhancement powder could contribute to the ionisation of species contained within the fingermark residue. In order to exclude this possibility , an additional experiment was conducted comparing the MS spectra and the MS images of two halves of the same natural mark, both treated with carbon black though only one half was subsequently sprayed using the MALDI matrix.…”
Section: Throughout the Experiments Performed Usingmentioning
confidence: 99%
“…This demonstrates that flavone is a more effective matrix than the 'traditional' across the range of matrices tested, is given in The use of CG as a matrix for LMW MALDI has already been studied extensively by the authors' research group. 19 In this study, the peaks observed in the positive ion mode with CG were dominated by the singly charged naked metal cations, cation oxides and carbides. nor which anion is present.…”
Section: Resultsmentioning
confidence: 59%